Implementasi Kebijakan Peraturan Daerah Kota Surabaya No 3 Tahun 2023 Tentang Perlindungan Anak Berbasis Rumah Anak Prestasi Di Kota Surabaya - Tri Setiyowati, Tiara; Darmawan, Arif; Basyar, Muhammad Roisul (Policy and Maritime Review, 2024)
Child protection treatment that has been regulated in the Surabaya City Regional Regulation Policy No. 3 of 2023 concerning child protection. The content of the policy also regulates the protection of children with special needs to get special needs met, equal rights, the same behavior as other children to achieve full social integration and get social assistance. The city of Surabaya which received the award as a Child-Friendly City for five consecutive times. In realizing the protection of children with special needs based on the achievement children's home program which was inaugurated in 2022 on Jl. Nginden Semolo no.23. Qualitative research with a descriptive approach aims to find out how the implementation of child protection policies in the city of Surabaya. The data collection process obtained from interviews, observations and documents is used as research data analysis. The policy implementation model according to Mazmanian and Sabatier is based on three influencing variables. The results of this study show that the implementation of child protection policies based on achievement children's homes in the city of Surabaya is running according to the content of the policy. Participation from implementing officials and commitment to improve service quality.